Evaluation of anti-Helicobacter pylori antibodies level in sera of patients with chronic hepatitis B - Shiamaa G. Abid; Rana S. Aboud; Safa A. Abudl-Razak; Anmar S. Aboud (World Journal of Experimental Biosciences, 2015)
The relationship between chronic hepatitis B virus and Helicobacter pylori infection was evaluated to determine, seventy five patients with chronic hepatitis B infection (8-70 years) were investigated. The results were compared with the results of 50 healthy volunteers. Anti-H. pylori antibodies IgA and IgG were measured by Indirect fluorescent antibody test (IFAT) in sera of patients and healthy groups. The percentage of anti-H.pylori IgA antibodies (26.67%) were significantly (P 0.05). The present results indicated that the acute infection with H. pylori may be correlated with severity of chronic hepatitis B infection.
Keywords: Hepatitis B virus, Chronic infection, Helicobacter pylori, Antibodies.